Możliwości uprawiania i rozwoju turystyki aktywnej w Euroregionie Karpackim - Bogusz, Kazimierz (The Role and Place of Polish Spa Resorts in the Development of Health Care, Relaxation and Tourism in the Karpacki Euroregion, 2005)
Karpacki Euroregion was brought into being in 1993. Euroregion includes Karpackie areas near the border of Poland, Slovakia, Ukraine, Hungary and Romania. The purpose of Euroregion functioning is development of economic and cultural cooperation, as well as, protection of unique nature of Karpaty. Taking advantage of outstanding natural conditions of this area, its economy, as well as, world-wide trend in development of tourism, various kinds and forms of active qualified and technicall tourism is preferred to pursue.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 97-104